(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The methods and techniques used in modern concepts of management (ISO and TQM) accelerate the procedures of adjustment of an enterprise to the changing commercial environment. This is particularly important for Polish enterprises, which are facing an additional challenge in dealing with international competitors. Managers are compelled to make proactive decisions involving the taking of corrective and preventive actions. The dynamics of this phenomenon are compatible with Deming’s conception of constant improvement - PCDA. The standard norms offer excellent methods that facilitate balancing environmental factors against internal organizational activities. The most effective methods are benchmarking, outsourcing. The improvement of an enterprise is conditioned by common actions undertaken by both management and workers as these common actions guarantee the effectiveness of the implemented methods and techniques. Also of great significance are well-balanced contacts between suppliers and external clients.